Absolute divorce in Argentina, 1954-1956: Debates and practices regarding a short-lived law - Valobra, Adriana María (2013)
This article examines the formulation, application, and effects of Article 31 of Law 14.394, which introduced absolute divorce into Argentina, albeit briefly: the law was passed in December 1954 and 'suspended' in March 1956. Our study sheds light on the juridical dimension of a topic that has not been considered to date. We present the results of our research in two parts. The first part analyzes the text of the law and the debates around it in Argentina's Congress. The second part provides an overview of divorce sentences and then considers certain exceptional cases. The specific features of the debates and sentences considered here provide a more complex vision of Juan Domingo Perón's government's definitions of the "new family".